2000
DOI: 10.1128/jb.182.2.513-517.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Amino Terminus of Salmonella enterica Serovar Typhimurium ς 54 Is Required for Interactions with an Enhancer-Binding Protein and Binding to Fork Junction DNA

Abstract: (20,28).Interactions between 54 -holoenzyme and enhancer-binding proteins are transient, and little is known about the nature of these interactions. The C 4 -dicarboxylic acid transport protein D (DctD) is an enhancer-binding protein from Sinorhizobium meliloti that can be cross-linked to 54 and the ␤ subunit of RNA polymerase (16). Some mutant forms of DctD that fail to activate transcription also fail to cross-link to these subunits (27), suggesting that DctD contacts these subunits of 54 -holoenzyme to cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…0.6 ml of the resulting extracts were mixed with 2 μl of rabbit anti-serum against S . Typhimurium σ 54 [ 73 ] and incubated with gentle shaking overnight at 4°C. The next day, 50 μl of protein A-Sepharose bead slurry was added to each sample, incubated 1 hr at room temperature and collected by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…0.6 ml of the resulting extracts were mixed with 2 μl of rabbit anti-serum against S . Typhimurium σ 54 [ 73 ] and incubated with gentle shaking overnight at 4°C. The next day, 50 μl of protein A-Sepharose bead slurry was added to each sample, incubated 1 hr at room temperature and collected by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the DctD C3 mutants (in both the ESELF and the GAFTGA motifs) failed to activate transcription (Wang et al , 1997). Use of σ 54 with Region I deleted showed that σ 54 Region I was dispensable for binding DctD in the cross‐linking assay (Kelly and Hoover, 2000). In direct contrast to these results, the nucleotide‐dependent activator‐σ 54 binding assay using the transition state analogue ADP.AlF x showed that σ 54 Region I was essential for stable binding to PspFΔHTH and the central domain of NifA (Chaney et al , 2001).…”
Section: Binding Interactions Between Activator and σ54mentioning
confidence: 99%
“…Nonetheless, holoenzyme binds tighter than does 54 alone. Two other regions can affect the affinity of binding: the N terminus plays complex multiple roles in binding to both duplex and melted DNA (10,17,41,52,59,60,98,117), and the segment between the C terminus and the major core-binding determinant influences binding affinity (12,50). These regions do not necessarily make direct DNA contact.…”
Section: Domain Structure Promoter Recognition and Core Interactionsmentioning
confidence: 99%
“…This is accomplished using the ATPase activity of the activator, which loops from the enhancer site (96). The interactions between activator and the 54 -RNA polymerase holoenzyme appear to be transient, and the only direct physical evidence has been by a cross-linking assay using the DctD activator (60,69).…”
Section: Mechanism Of Promoter Activationmentioning
confidence: 99%